A Meta‐Analysis of the Association of Fracture Risk and Body Mass Index in Women. (January 2014) - Johansson, Helena; Kanis, John A; Odén, Anders; McCloskey, Eugene; Chapurlat, Roland D; Christiansen, Claus; Cummings, Steve R; Diez‐Perez, Adolfo; Eisman, John A; Fujiwara, Saeko; Glüer, Claus‐C; Goltzman, David; et al.
ABSTRACT Several recent studies suggest that obesity may be a risk factor for fracture. The aim of this study was to investigate the association between body mass index (BMI) and future fracture risk at different skeletal sites. In prospective cohorts from more than 25 countries, baseline data on BMI were available in 398, 610 women with an average age of 63 (range, 20–105) years and follow up of 2.2 million person‐years during which 30, 280 osteoporotic fractures (6457 hip fractures) occurred. Femoral neck BMD was measured in 108, 267 of these women. Obesity (BMI ≥ 30 kg/m2) was present in 22%. A majority of osteoporotic fractures (81%) and hip fractures (87%) arose in non‐obese women. Compared to a BMI of 25 kg/m2, the hazard ratio (HR) for osteoporotic fracture at a BMI of 35 kg/m2 was 0.87 (95% confidence interval [CI], 0.85–0.90). When adjusted for bone mineral density (BMD), however, the same comparison showed that the HR for osteoporotic fracture was increased (HR, 1.16; 95% CI, 1.09–1.23). Low BMI is a risk factor for hip and all osteoporotic fracture, but is a protective factor for lower leg fracture, whereas high BMI is a risk factor for upper arm (humerus and elbow) fracture. When adjusted for BMD, low BMI remained a risk factor for hip fracture but was protective for osteoporotic fracture, tibia and fibula fracture, distal forearm fracture, and upper arm fracture. When adjusted for BMD, high BMI remained a risk factor for upper arm fracture but was also a risk factor for all osteoporotic fractures. The association between BMI and fracture risk is complex, differs across skeletal sites, and is modified by the interaction between BMI and BMD. At a population level, high BMI remains a protective factor for most sites of fragility fracture. The contribution of increasing population rates of obesity to apparent decreases in fracture rates should be explored. © 2014 American Society for Bone and Mineral Research.